2020
DOI: 10.32996/ijllt.2020.3.6.8
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Reading Proficiency: A Case Study of a Moroccan High School

Abstract: The present study explores students’ primary concerns, perceptions, difficulties and attitudes characterized by a sheer lack of motivation towards reading. It also demonstrates how a language teacher can prosper in his/her own undertaking to bring about a community of readers with a want to read. This study covers an important comparison between students of three different levels, namely Common Core, First and Second year Baccalaureate. Likewise, it tries to explore the extent to which unmotivated readers are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 2 publications
0
0
0
Order By: Relevance
“…This research employed translation tests to obtain the results needed for the research. The translation test utilized was adapted from Langga & Alico's (2020) study. The outputs of the participants were evaluated using the framework of Gass & Selinker (2008) that involves a five-step procedure: collection of data, identification of errors, quantification of errors, analysis of source of errors, and remediation.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…This research employed translation tests to obtain the results needed for the research. The translation test utilized was adapted from Langga & Alico's (2020) study. The outputs of the participants were evaluated using the framework of Gass & Selinker (2008) that involves a five-step procedure: collection of data, identification of errors, quantification of errors, analysis of source of errors, and remediation.…”
Section: Methodsmentioning
confidence: 99%
“…In the study of Langga and Alico (2020), it revealed that the participants also commit the same error.For instance, the phrase "…nagsasagawa ng teknolohikal na interbensiyon ang mga siyentista…" was translated "…scientist conduct of technology that intervention…" The example, "ang mga siyentista" suggests that the subject is plural because of the determiner "mga", which requires a plural verb. The error revealed that the participant did not consider the rule of subject-verb agreement because there is no such rule in the SL.…”
Section: Subject-verb Agreement Source Textmentioning
confidence: 97%
See 3 more Smart Citations